2021
DOI: 10.1177/1468087420988191
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of the effect of temperature on ignition of modified kerosene

Abstract: Kerosene based hydrocarbon fuels are preferred candidates for the source of energy due to its stable properties. Based on the requirement of the combustor and the growing concern over pollutant, kerosene based fuels are modified. The fuel under investigation is a modified form of kerosene with ultra-low sulphur content. The effect of temperature on modified kerosene is studied for viscosity, surface tension, specific heat, density and ignition delay. The time delay for ignition of gas-phase mixtures of modifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…2 (approximately the driven and driver section have the same length). In contrast, diaphragm position‐1 and position‐3 models were pretty ideal in finding the IDT of Diesel fuels, as they provided a high Mach number and high reflected wave temperature values as in the references 48‐55 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 (approximately the driven and driver section have the same length). In contrast, diaphragm position‐1 and position‐3 models were pretty ideal in finding the IDT of Diesel fuels, as they provided a high Mach number and high reflected wave temperature values as in the references 48‐55 …”
Section: Resultsmentioning
confidence: 99%
“…Diaphragm pressure ratio vs. incident Mach number (M i ) F I G U R E 1 0 Incident Mach number dependency on diaphragm location and pressure ratioMach number and high reflected wave temperature values as in the references[48][49][50][51][52][53][54][55] …”
mentioning
confidence: 99%
“…Kerosene or paraffin may be a feasible choice. Justin Sundararaj et al [ 95 ] indicated that with the increase in the temperature from 26 to 60 °C, the viscosity of modified kerosene with the density of approximately 0.80 g/cc decreased from 1.33 to 0.90 cP.…”
Section: Prospectsmentioning
confidence: 99%
“…The scramjet engine has gained a lot of attention in recent decades as a viable candidate for future hypersonic propulsion vehicles. [1][2][3][4] Fuel injection, mixing, and combustion are the scramjet engine's main challenges, particularly for heavy hydrocarbon fuels 5 that need a relatively long time for chemical reactions to continue. The well-known propulsion concepts pursued scramjet applications are the Dual-mode Combustion Ramjet (DMCR) and Dual Combustion Ramjet (DCR).…”
Section: Introductionmentioning
confidence: 99%